The Effect of 12 Weeks of Strength Training on Muscular Strength, Body Fat Percentage, Irisin and BDNF in Active Middle-aged Women - Reavan Afshar; Masoud Rahmati; Rahim Mirnasouri (Majallah-i dānishgāh-i ̒ulūm-i pizishkī-i Arāk)
Introduction: Considering the synthesis and secretion of irisin and BDNF from muscle tissue during exercise and the possible relationship of these factors with improving muscle strength and performance, the present study aimed to investigate the effect of 12 weeks of strength training on muscle strength, body fat percentage, irisin, and BDNF in inactive middle-aged women. Methods: In a semi-experimental study, 20 inactive middle-aged women (mean age 37.70 ± 5.91 years, weight 79.80 ± 5.82 kg) were selected and randomly assigned to two strength training groups (n = 10) and control groups (n = 10). The training group performed 12 weeks of strength training, three sessions per week at an intensity of 65 to 80% of maximum strength. Then, blood samples were taken using ELISA to measure irisin and BDNF. Independent t-test and Pearson correlation test were used to analyze the data. The significance level (P ≤ 0.05) was considered. Results: Strength training significantly increased serum irisin concentration (P = 0.035) and serum BDNF concentration (P = 0.058) and also considerably decreased body fat percentage (P = 0.058) in middle-aged women. There was also a positive and significant relationship between lower body strength and serum irisin levels (P = 0.040). The Results from the Pearson correlation test indicate a significant positive relationship between BDNF and upper body strength (P = 0.038). Conclusions: Based on the results of the present study, it seems that increased secretion of serum irisin and BDNF hormones is related to increased muscle strength following strength training in middle-aged individuals.